Involving Culture in English Language Learning - Muhammad Mujtaba Mitra Zuana (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2017)
Nowdays, culture takes a significant role in language teaching and learning. It happens when the universal communication has become the reality that cannot be ignored. The border of countries, in terms of communication, is not relevant anymore. Surely, there will be cross cultural phenomenon when people from different background communicate each other. Hence, need of the learners is not only about their linguistic knowledge, but also the use of language involving cross cultural understanding in real life circumstances. In line with this situation, Indonesia’s 2013 curriculum emphasizes cultural understanding in language teaching and learning. It is expected that the learners have no difficulties in communication which may consist of cultural aspects. Understanding the cultural aspects in communication make them achieve meaningful communication in which the knowledge and the use of language including culture are not separated. This paper discusses information about the relationship between culture and language teaching and learning, the principles of involving culture in language teaching and learning, and the involvement of culture in English subject of 2013 Curriculum as well.